Medium‐Chain Acyl‐CoA Dehydrogenase Deficiency in Adulthood: A Potential Diagnosis in a Patient with Mental Status Changes Suspected of Drug Toxicity. Issue 4 (July 2015) - Randall, Morgan; Rolf, Cristin; Gibson, Stephanie Mayfield; Hall, Patricia L.; Rinaldo, Piero; Davis, Gregory J.
Abstract Medium‐chain acyl‐CoA dehydrogenase (MCAD) deficiency is a rare but important component of the differential diagnosis for adults with a history of premortem mental status changes and the postmortem finding of hepatic steatosis. This case report describes a 30‐year‐old white man who, following a period of nausea and vomiting, was admitted to the hospital with sudden mental status deterioration followed rapidly by clinical deterioration and death. Treating physicians in this case suspected acute illicit drug toxicity with synthetic cathinones based on social history. Clinicians and medical examiners should be aware that the presentation, signs, and symptoms described may indicate an underlying inborn error of metabolism such as MCAD deficiency and take action accordingly.